Modern biomass-based transportation fuels from pyrolysis process, bio-ethanol, bio-methanol and bio-diesel - Mohd Badli, Muhammad Faizul Amri; Vicknasparran, Adam Nasuha; Khalid, Amir; Mustaffa, Norrizal; Ngadiron, Zuraidah; Mohamed Sunar, Norshuhaila (Penerbit UTHM, 2020)
In this paper, the modern biomass-based transportation fuels such as fuels from Pyrolysis process, bio-ethanol, bio-methanol, and bio-diesel are briefly reviewed. Here, the term bio-fuel and non-organic fuel is referred to as liquid or gaseous fuels for the transport sector that are predominantly produced from biomass. There are several reasons for bio-fuels and non-organic fuel to be considered as relevant technologies by both developing and industrialized countries. They include energy security reasons, environmental concerns, foreign exchange savings, and socioeconomic issues related to the rural sector. The term modern biomass is generally used to describe the traditional biomass use through the efficient and clean combustion technologies and sustained supply of biomass resources, environmentally sound and competitive fuels, heat and electricity using modern conversion technologies. Modern bio-mass can be used for the generation of electricity and heat. Bio-ethanol, bio-methanol and bio-diesel as well as diesel produced from biomass by Pyrolysis process are the most modern biomass-based transportation fuels. Bio-ethanol is a petrol additive/substitute.